Full‐Color Inorganic Carbon Dot Phosphors for White‐Light‐Emitting Diodes. Issue 19 (28th July 2017) - Tian, Zhen; Zhang, Xutao; Li, Di; Zhou, Ding; Jing, Pengtao; Shen, Dezhen; Qu, Songnan; Zboril, Radek; Rogach, Andrey L.
Abstract : Light‐emitting carbon dots (CDots) are widely investigated due to their distinct merits. However, it is still a challenge to modulate their bandgap emissions and conquer their aggregation‐induced luminescence quenching to achieve full‐color highly emissive CDot‐based phosphors. Herein, this study proposes an approach toward realization of full‐color emissive CDots from two common precursors, citric acid and urea, through employing three different solvents (water, glycerol, and dimethylformamide) and their combinations in a solvothermal synthesis. Employing sodium silicate solution, this study further demonstrates the microwave‐assisted method allowing to incorporate CDots into a silica network, which effectively prevents aggregation of CDots and results in strongly luminescent full‐color inorganic CDot phosphors with photoluminescence quantum yields of 30–40%. Through deposition of the red‐ and green‐emitting CDot phosphors on blue‐emitting InGaN chips, white‐light‐emitting diodes are fabricated with Commission Internationale de L'Eclairage of (0.34, 0.31) and the color rendering index of 82.4, indicating their promising application for solid‐state lighting. Abstract : Full‐color luminescent carbon dots (CDots) are developed from citric acid and urea by varying solvents in solvothermal synthesis. Based on these CDots, full‐color inorganic CDot phosphors with photoluminescence quantum yields in the range of 30–40% are realized in microwave assisted treatment of the CDots sodium silicate aqueous solutions, which pave the way for achieving white light CDot‐based light‐emitting diodes with Commission Internationale de L'Eclairage of (0.34, 0.31) and the color rendering index of 82.4.